The Use Of Code-mixing by Nathalie Kezia in Indonesia’s Next Top model cycle 3 - Amalia, Annisa; Heryono, Heri (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2024)
This research aims to categorize the types and functions of code mixing used by one of the contestants in Indonesia’s Next Top Model Cycle 3, Nathalie Kezia. This research used a descriptive-qualitative method to analyze the conversation. The data source was taken from a YouTube channel entitled “Indonesia’s Next Top Model Cycle 3”. The result showed there are three types of code mixing found in the total 43 data; 35 of insertion (82%), 4 of alternation (9%), and 4 of congruent lexicalizations (9%). In the data analyzed, the most dominant type of code mixing is insertion, which indicates that Nathalie frequently inserts one language into another in her utterances. Moreover, it is clear from the findings that Nathalie Kezia used code mixing with several functions, which are 30 data of ‘talking about a particular topic’ (70%), 3 data of ‘being emphatic about something’ (7%), 8 data of ‘interjection’ (18%), and 2 data of ‘intention of clarifying the speech content for the interlocutor’ (5%).